Policy Implementation Study Mandatoryspending on Education Function in Jembrana District - Diendi, I Gede Gus; Widnyani, Ida Ayu Putu Sri; Afandi, Muhamad Nur (Fakultas Ekonomi Universitas Pendidikan Ganesha, 2024)
The mandatory spending policy for the education function in Indonesia is mandated by Article 31(4) of the 1945 Constitution and Article 49(1) of Law No. 20/2003 on the National Education System, requiring a minimum allocation of 20% from both the State Budget (APBN) and Regional Budget (APBD). This research aims to examine the implementation of this policy in Jembrana Regency through a descriptive qualitative approach. Data were collected via observations, interviews, and document analysis. The study applied the policy implementation framework of Van Meter and Van Horn and used the Miles and Huberman model for data analysis. Results indicate that Jembrana has fulfilled the 20% minimum allocation requirement. However, most of the budget is used for personnel expenditure, with limited allocation for capital investment. As a result, 25% of primary schools remain in disrepair. Despite these challenges, strong political, social, and economic support exists among stakeholders. To address implementation issues, the study suggests optimizing local revenue, improving spending efficiency, reallocating goods and services budgets toward capital expenditure, and setting clear limits on personnel and capital expenditures. These measures aim to enhance the quality and equity of education infrastructure and service delivery in the region.